IMPROVED INTERPERSONAL INTELLIGENCE MODEL STUDENTS THROUGH COOPERATIVE LEARNING (TYPE two stay two stray) IN LEARNING IPS (Classroom Action Research in Class VIII C SMP Negeri 45 Bandung) - Dewi, Kania (International Journal Pedagogy of Social Studies, 2017)
Abstract-This research is supported by low interpersonal intelligence of learners on IPS learning in class VIII C SMP Negeri 45 Bandung. This can be seen from the still low empathy, prosocial, low self-awareness as a member of the group, social ethics of learners, problem-solving skills and effective communication skills of learners. Seeing the problem, the researcher chose Cooperative Learning Model Type Two Stay Two Stray (TSTS) as a solution to improve students' interpersonal intelligence. The purpose of this study is to describe the planning, implementation, obstacles and solutions and increase interpersonal intelligence. The type of research used is Class Action Research (PTK) Kemmis and Mc model. Taggart which consists of four stages. Stages of planning in this study include determining SK / KD and teaching materials, preparing RPP, Student Worksheet and create research instruments according to the needs of researchers. This research was conducted in three cycles and obtained the result of improvement of students' interpersonal intelligence in IPS learning. Increased interpersonal intelligence of learners is characterized by an increase that occurs in every aspect of the assessment of interpersonal intelligence. This proves cooperative learning model type two stay two stray (TSTS) can improve students' interpersonal intelligence.Keywords: Interpersonal Intelligence, Cooperative Learning Model type Two Stay Two Stray (TSTS).